United Republic of Tanzania : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement. (IMF Staff Country Reports; Country Report, 2005)
This paper discusses United Republic of Tanzania's Fourth Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. A principal challenge for monetary policy continues to be liquidity management in the face of high foreign aid inflows. A comprehensive Financial Sector Reform Implementation Action Plan has been completed. Under the plan, efforts to remove key structural impediments to broaden access to financial services will be accelerated, including measures to facilitate increased medium- and longer-term lending, and streamline the pension sector.